Evolutionary Comparison of the Developmental/Physiological Phenotype and the Molecular Behavior of SPIRRIG Between Arabidopsis thaliana and Arabis alpina - Stephan, Lisa; Jakoby, Marc; Hülskamp, Martin (Frontiers in Plant Science, 2021)
Beige and Chediak Higashi (BEACH) domain proteins mediate membrane-dependent processes in eukaryotic cells. The plant BEACH domain protein SPIRRIG in A. thaliana (AtSPI) was shown to display a similar molecular behavior as its yeast and animal homologs, along with a range of cell morphological defects. In addition, AtSPI was implicated in RNA metabolism in the context of salt stress responses. To determine, whether the dual function of SPI in apparently unrelated molecular pathways and traits is present in another Brassicaceae, we analyzed three Aaspi alleles in Arabis alpina. We show that the molecular behavior of the SPI protein is similar, suggesting that the dual function of SPI membrane-dependent processes and RNA metabolism is evolutionary conserved in Brassicaceae. Also, a dual function in cell morphogenesis and salt stress response is supported, though we observed distinct deviations in the phenotypic spectrum.